2019
DOI: 10.1111/jfbc.12940
|View full text |Cite
|
Sign up to set email alerts
|

Does unsaponifiable fraction of grape seed oil attenuate nitric oxide production, oxidant and cytotoxicity activities

Abstract: Triterpenoids, tocopherols, and phytosterols presented in unsaponifiable fraction of grape seed oil have several beneficial effects comprising antioxidant, anti‐inflammatory, and antitumor capacities. In this study, the unsaponifiable fraction of three Tunisian grape seed varieties (Vitis vinifera L.), namely Merlot, Carignan, and Syrah, was investigated. The identified compounds were two triterpenic compounds (β‐amyrin, lanosterol), six phytosterols (campesterol, ∆7‐avenasterol, stigmasterol, β‐sitosterol, β‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Several studies have shown that grape seed oil delays senescence by attenuating oxidative (Harbeoui et al. 2019 ) and inflammatory responses (Millan-Linares et al. 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that grape seed oil delays senescence by attenuating oxidative (Harbeoui et al. 2019 ) and inflammatory responses (Millan-Linares et al. 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…confirmed cytotoxicity and anti‐inflammatory effects of GSO unsaponifiable fraction (tocopherols, sterols, and triterpenoids). [ 13 ] In addition, GSO has been reported as a material with inhibitory effect on the growth of some pathogens ( Staphylococcus aureus and Escherichia coli) . [ 9 ] However, literature lacks studies conducted in order to examine GSO obtained from different varieties as well as against different microbial strains.…”
Section: Introductionmentioning
confidence: 99%
“…β-sitosterol represents the main sterol in grapeseed oil, and α-tocopherol represents the main tocopherol, reaching values of around 70% of tocopherols, corresponding to 3.8 mg/100 g of oil [ 18 ]. Taking into account the incorporation of GP into the studied foods could be interesting from a nutritional point of view due to the incorporation of unsaturated fatty acids and tocopherols/tocotrienols which are important antioxidant lipid compounds and have been associated with health-promoting effects [ 40 ].…”
Section: Resultsmentioning
confidence: 99%